Integrating USLE and GIS Techniques For Soil Erosion Hazard Mapping In Ijo Watershed - Afrilia Nur Fajriyah; Gangsar Edi Laksono; Eko Ahmad Riyanto; Arianti Mutia Ningrum; Fajar Firmansyah (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2025)
Soil erosion is a critical form of land degradation, particularly in tropical watersheds characterized by high rainfall intensity and steep topography. This study aims to assess erosion hazard levels in the Ijo Watershed, Central Java, Indonesia, by integrating the Universal Soil Loss Equation (USLE) with Geographic Information System (GIS) techniques. Five USLE factors—rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), land cover (C), and conservation practice (P)—were analyzed using multi-source data including rainfall records, soil maps, Digital Elevation Model (DEM), land cover maps, and field surveys. Results show that erosion hazard ranges from very low to very high, with the largest proportion in the very low category (35.09%) and the smallest in the very high category (8.74%). Areas with steep slopes and minimal conservation practices were identified as priority zones for intervention. The novelty of this study lies in applying the USLE–GIS approach to a small tropical watershed, which remains understudied despite its ecological and socio-economic importance. The findings not only fill knowledge gaps on erosion dynamics in small-scale watersheds but also provide scientific evidence for spatially explicit land management and conservation strategies. This contributes directly to Sustainable Development Goals (SDG 15) and Indonesia’s Land Degradation Neutrality (LDN) targets.